The Relationship of Body Mass Index in Third Trimester of Pregnancy with Low Back Pain Incidence - Henky, Jefri; Efriza; Aprillia (CV. AKBAR PUTRA MANDIRI, 2022)
Background: Low Back Pain is pain in the lower back which is a sign of disorder that causes a state of discomfort in performing daily activities and is felt in the anatomical area, especially in the fifth lumbal and sacral area. Low Back Pain will increase as gestational ages. This discomfort begins between the fifth and seventh months of pregnancy. Purpose: To find the relationship between body mass index in the third trimester of pregnancy with Low Back Pain incidence. Method: This research is an observational analytical research with cross-sectional approach. The population of this research is pregnant women in the third trimester who visited poly Obstetrics and Gynecology Hermina Padang Hospital with 77 samples by using consecutive sampling technique. Data analysis uses univariate and bivariate analysis with data processing using the computerized SPSS 23.0 version. Results: The most age were 26-35 years which is 44 people (57,1%), the most likely respondents were those who did not work which is 48 people (62,3%), and the most respondents gestational age is > 36 weeks that is 40 people (51,9 %). The average body weight of the respondent is 65.8277 kg with a minimum body weight 51.51 kg and maximum 80.40 kg. The average height of respondent is 157.99 cm with a minimum height 148 cm and maximum 170 cm. The majority of respondents with an overweight body mass index were 50 people (64,9%), the highest level of LBP pain is 2 (a little pain) which is 26 people (33,8%), with respondents experienced LBP of 61 people (79,2%). Based on the bivariate analysis, it is known that there is a relationship between body mass index in the third trimester of pregnancy with Low Back Pain incidence (p=0.022). Conclusion: The third trimester of pregnant women, the most age is early adulthood (26-35 yars), with the most work is not working, and the most gestational age >36 weeks. The average body weight of the respondent is 65.8277 kg and the average height of the respondent is 157.99cm, the most body mass index is overweight, the highest level of LBP pain is 2 (a little pain), and in the third trimester pregnant women experience the most LBP incidence is yes and there is a relationship between body mass index in the third trimester of pregnancy with low back pain incidence.